Transit Hotel in Transit Oriented Development Area - Achmad Delianur Nasution; Ronaldo Immanuel Lubis (International Journal of Architecture and Urbanism, 2018)
According to the Presidential Regulation of the Republic of Indonesia Number 62 The year 2011 on Spatial Plans of Medan, Binjai, Deli Serdang and Karo (Mebidangro), Pinang Baris was included in TOD Route Map. The commercial area will be redesigned by the division of each building function, corresponding to one of TOD's four segmentation divisions [1]. The building designed in this commercial area is a transit hotel due to its location right next to Pinang Baris Terminal, with the dominance of visitors with tourist destinations to Berastagi, Bukit Lawang, Tangkahan, Lake Toba or Aceh. Hotel Transit Pinang Baris is right in front of T.B Simatupangmain street, adjacent to Mall Pinang Baris, and fitted with Pinang Baris Market building. Inter-building integration will be applied to support the factor of commercial function in the built area. By raising the "Global Warming" Issues, the Pinang Baris Transit Hotel will apply the green architecture concept on a 2.7-hectare site area, with 1.1-hectare of land built, and overall 26.746m2 building area and a maximum height of 4 floors according to local regulations. Then the hotel will be systematically designed using Glass-Box Method with form following hotel's site and standard. From the analysis, the hotel is a 3-star hotel. The transit hotel has 128 rooms, with 120 rooms of 6x4m standard size and eight rooms of 6x6m Deluxe size. Additional facilities are available at this Transit Hotel, by 3-star standards, i.e., coffee shop, bar, swimming pool, fitness, spa & sauna, and a ballroom. Thus Transit Pinang Baris Hotel with its implementation can be a place to stay that can meet the needs of visitors in the commercial area TOD Pinang Baris.